The use of floorball in adaptive physical education of schoolchildren with intellectual disabilities - Gerasimov E.A. (Theory and Practice of Physical Culture, 2024)
The purpose of the study. To determine the composition of the funds and establish a rational sequence of teaching basic technical elements of floorball to children with intellectual disabilities (IN). Methodology and organization of the study. The means and a specific procedure for teaching the basic elements of the floorball technique to children with intellectual disabilities are proposed. An experimental approbation was carried out with the participation of four groups of schoolchildren who studied using different methods. The results of the study and conclusions. The effectiveness of the author’s approach in teaching basic techniques in floorball to students with intellectual disabilities is scientifically substantiated.